The impact of nurses’ caring behaviors and personality traits on workplace violence - Chang, Hongjuan; Liu, Xin; Hu, Mengmeng; Zeng, Rui; Zhang, Chun; Luo, Huanhuan (Frontiers in Psychology, 2025)
AimsBased on the propensity score matching method, this study analyzes the correlation between nurses’ exposure to workplace violence, caring behaviors, and personality traits. The analysis provides a foundation for developing individualized strategies to prevent workplace violence among nurses.MethodsConvenience sampling was conducted from February to June 2024 in Grade 3A hospitals across 11 Chinese provinces. The study utilized the Workplace Violence Frequency Measurement Scale, Caring Behaviors Inventory, and Ten-Item Personality Inventory for data collection. The analysis employed propensity score matching to pair nurses experiencing low-frequency workplace violence with those experiencing high-frequency workplace violence in a 1:2 ratio, controlling for confounding variables. The associations between personality traits, caring behaviors, and workplace violence were then analyzed.ResultsFollowing propensity score matching to control for baseline information, the analysis included 622 nurses (403 in the low-frequency exposure group and 219 in the high-frequency exposure group). The findings revealed respect and connectedness (OR = 0.946, 95.0% CI: 0.912 ~ 0.981), emotional stability (OR = 0.814, 95.0% CI: 0.711 ~ 0.906) as negative predictive effects, and openness as a positive predictive effect (OR = 1.250, 95.0% CI: 1.065 ~ 1.398).ConclusionNurses demonstrating patient respect and maintaining close contact, along with those exhibiting emotional stability, experience low-frequency exposure to workplace violence; conversely, nurses with more open personalities experience higher frequency exposure. These findings suggest the importance of enhancing nurses’ caring behaviors and implementing personality-specific training programs to address workplace violence.